New urban-rural interface: Agricultural cooperatives for urban-rural interaction in China - Yuheng Li (European Regional Science Association (ERSA), 2010)
Recently, urban-rural linkages have been increasingly gaining momentum in the economic development and poverty alleviation in urban and rural areas. However, flows of people, goods, capital and information between urban and rural areas can be beneficial or detrimental to either urban or rural areas. Thus, it is important to manage these flows. Small and medium-sized towns are considered as a positive role of being the urban-rural interface through which modernization and wealth trickle down from cities to villages, especially in the process of decentralization and urbanization. Nevertheless, the paper argues that small and medium-sized towns at the peri-urban or urban fringe merely serve as the extension of urban influence over rural areas since rural peasants are disorganized and often passively affected by such influence. The aim of this paper is to explore agricultural cooperatives acting as a new type of urban-rural interface in China. Through comparison with small towns, the paper considers agricultural cooperatives as dynamic, rural-favored and space-beyond interface through which urban-rural linkages are strengthened and rural development is further promoted. The framework of agricultural cooperatives being the new type of urban-rural interface is depicted. The paper stresses the necessity of developing agricultural cooperatives to intensify the urban-rural interaction in the Chinese context of major rural population.
Keywords: 330